Role of medical thoracoscopy in the management of parapneumonic effusion and empyema thoracic - Ansari, Abdul Qayyum; Bansiwal, Babulal; Saxena, Anil; Sharma, Hemant Kumar; A., Shinu (International Journal of Research in Medical Sciences, 2020)
Background: The treatment modality use in early pleural empyema mainly depends on the antimicrobial therapy along with thoracocentesis. In case of complicated empyema this modality does not work and lung not fully expand, until removal of adhesions. The main purpose of the current study is to analyze the experience of management of complicated parapneumonic effusion and empyema thoracic through rigid medical thoracoscopy under local anaesthesia. Aim and objective is to study the role of medical thoracoscopy in the management of empyema thoracic and parapneumonic effusion at tertiary health centre. Methods: This is a descriptive case series study in which 49 patients were recruited, who have clinically and radiologically show empyema thoracic, from department of Respiratory medicine, GMC, Kota, Rajasthan. All patients underwent medical thoracoscopy under local anesthesia. Written Informed consent was taken from the study participants. Ethical approval was obtained from Ethical Review Committee of the hospital. Patients who have HIV and Hbsag positive, those with multiple organ failure and bleeding disorders were excluded. Results: Total 49 patients, out of them 41(84%) were male and 8(16%) were female with mean age 45 years (range 18 to 70 years). Final evolution through chest x-ray revealed complete resolution or successful thoracoscopy done in 37 case of fibrinopurulent (92.50%) and 5 cases of organizing empyema (55.56%). overall success rate 85.71%. Total 7 cases (3 case of fibrinopurulent and 4 cases of organizing empyema) refer to higher center for decortications. Conclusions: Medical Thoracoscopy under local anaesthesia is a safe procedure, efficient and cost-effective intervention for early management of complicated empyema, particularly in early stage of empyema (fibro purulent).